2022
DOI: 10.1186/s13578-022-00772-z
|View full text |Cite
|
Sign up to set email alerts
|

MIR210HG promotes breast cancer progression by IGF2BP1 mediated m6A modification

Abstract: Background Breast cancer is the most common cancer in women around the world, and the molecular mechanisms of breast cancer progression and metastasis are still unclear. This study aims to clarify the function and N6,2′-O-dimethyladenosine (m6A) regulation of lncRNA MIR210HG in breast cancer. Results High expression of MIR210HG was confirmed in breast cancer. MIR210HG promoted breast cancer progression, which was mediated by its encoded miR-210. MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The decisive role of m6A modification in cancer progression has been widely reported in recent years 19 , 45 . m6A modification is dynamically regulated by its writers, erasers, and readers, which are involved in the progression of cancer metastasis 13 , 16 , 46 , including BC 15 , 47 - 50 . Here, we found that the m6A reader IGF2BP1 was upregulated in BC tissues, especially BC metastatic lesions, and was associated with a poor prognosis of BC.…”
Section: Discussionmentioning
confidence: 99%
“…The decisive role of m6A modification in cancer progression has been widely reported in recent years 19 , 45 . m6A modification is dynamically regulated by its writers, erasers, and readers, which are involved in the progression of cancer metastasis 13 , 16 , 46 , including BC 15 , 47 - 50 . Here, we found that the m6A reader IGF2BP1 was upregulated in BC tissues, especially BC metastatic lesions, and was associated with a poor prognosis of BC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pancreatic cancer, MIR210HG can also promote various cancer types, such as breast cancer, gastric cancer, and ovarian cancer (53)(54)(55). Additionally, previous studies have identified seven GT-related lncRNAs as prognostic factors in colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, MIR210HG acted as oncogenic regulator and promoted pancreatic cell proliferation and migration ( 52 ). In addition to pancreatic cancer, MIR210HG can also promote various cancer types, such as breast cancer, gastric cancer, and ovarian cancer ( 53 55 ). Additionally, previous studies have identified seven GT-related lncRNAs as prognostic factors in colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 , 44 m 6 A methylation relies on the readers such as YTHDC2 and other m 6 A recognition proteins including heterogeneous nuclear ribonucleoprotein A2B1, heterogeneous nuclear ribonucleoproteins C, fragile X mental retardation protein, IGF2BP , and many others. 45 , 46 , 47 , 48 , 49 , 50 , 51 …”
Section: A Rna Methylation Modificationmentioning
confidence: 99%